Measurements of tumor size using CT and PET compared to histopathological size in non-small cell lung cancer - Funda Aydın; Levent Dertsiz; Evrim Sürer Budak; Akın Yıldız; Gülay Özbilim; Fırat Güngör (Diagnostic and Interventional Radiology, 2013)

(untitled)
PURPOSEIn this study, we aimed to compare the tumor sizes determined by maximum morphological computed tomography (CT) and functional positron emission tomography (PET) with the histopathological size to determine which method provides the best correlation with the histopathological size in lung carcinoma patients.MATERIALS AND METHODSForty lung carcinoma patients (39 males, one female) diagnosed histopathologically from surgical resection materials were included in this retrospective study. The mean age (±standard deviation, SD) of the patients was 67.8±10.3 years with a range of 44 to 81 years. The PET scans were performed within the same week as the CT scan. In the CT scans, the morphological tumor sizes were measured three-dimensionally by the longest transaxial section in the parenchymal and mediastinal screening window. The functional tumor sizes were also measured three-dimensionally in the PET scans. These two measurement values were compared with the histopathological size using Bland-Altman plotting. Bland-Altman plotting was also performed to define the 95% limits of agreement, which was presented as the bias ±1.96 SD.RESULTSThe histopathological sizes were measured in a range of 1.2 to 7.5 cm. The maximum measurement of the tumors on the CT scans showed a lower concordance (mean difference, -0.30) than that obtained from PET, and the SD was found to be larger than the PET (1.96 SD was 3.50 for CT and 2.50 for PET).CONCLUSIONThe PET measurements of tumor size were more compatible with the histopathological sizes than the CT measurements in patients with non-small cell lung cancer.